2013
DOI: 10.1136/bmjqs-2012-000952
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional education in team communication: working together to improve patient safety

Abstract: Effective team communication is important in patient safety. We demonstrate positive attitudinal and knowledge effects in a large-scale interprofessional TeamSTEPPS-based training involving four student professions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
207
0
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(226 citation statements)
references
References 37 publications
(21 reference statements)
6
207
0
13
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] While these IPE experiences are nonstandardized and site-dependent, the majority of them have shown positive effects on student attitudes toward interdisciplinary teamwork. [3][4][5][6][8][9][10][11][12] Similar to other health fields of study, US pharmacy programs have been charged with incorporating IPE into their curriculum. The Accreditation Council for Pharmacy Education (ACPE) recently set forth revised Standards to include IPE initiatives as part of the criteria for accreditation.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] While these IPE experiences are nonstandardized and site-dependent, the majority of them have shown positive effects on student attitudes toward interdisciplinary teamwork. [3][4][5][6][8][9][10][11][12] Similar to other health fields of study, US pharmacy programs have been charged with incorporating IPE into their curriculum. The Accreditation Council for Pharmacy Education (ACPE) recently set forth revised Standards to include IPE initiatives as part of the criteria for accreditation.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted TeamSTEPPS training with 306 students of medicine, nursing, pharmacy and medical assistants. The results showed that there were signifi cant improvements in the attitudes related to team communication, motivation, utility of training and self-effi cacy, team structure, monitoring the situation and mutual support (18) . One of the dimensions, "working conditions" presented the biggest weakness in the professional evaluations.…”
Section: Discussionmentioning
confidence: 92%
“…The Department of Defense Patient Safety Program in collaboration with the Agency for Healthcare Research and Quality (ARHQ) created the programme Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS), which is a system of teamwork based on evidence to improve the communication and teamwork skills of health professionals (17)(18) . Studies have been conducted using this programme to ascertain its eff ectiveness and benefi ts for patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Good communication skills enable pharmacists to establish effective relationships with patients and health care teams, contributing to the optimization of health outcomes and promotion of interprofessional relationships. 2,[4][5][6][7] While communication skills remain imperative for patient care in pharmacy practice, increasingly communication training is focused on the need for pharmacists to communicate competently with other health professionals. 2,8,9 Inadequate communication among health professionals can result in misunderstandings, negatively affect interprofessional relationships, cause suboptimal information transfer, and adversely affect health outcomes.…”
Section: Introductionmentioning
confidence: 99%